BUGIS FOLK SONGS IN THE DIGITAL ERA: TRANSFORMATION, PRESERVATION, AND COMMODIFICATION OF ORAL CULTURE ON DIGITAL PLATFORMS - Muhsyanur, Muhsyanur (HISKI, 2025)
This study explores the transformation, preservation, and commodification of Bugis folk songs in the digital era. As a form of oral culture, Bugis folk songs have undergone significant changes through their exposure on digital platforms such as YouTube and social media. Using a qualitative approach, data were collected through observation, in-depth interviews, and document analysis. The findings reveal that digitalization facilitates the preservation of folk songs via audiovisual recordings, but it also shifts the meaning and cultural functions of these oral traditions due to commodification. The songs are no longer solely cultural heritage artifacts but have become digital economic products. This study highlights the need for a balance between preserving cultural values and adapting to the dynamics of the digital economy.Keywords: oral culture, folk songs, digitalization, commodification Abstrak Penelitian ini mengkaji transformasi, pelestarian, dan komodifikasi lagu-lagu rakyat Bugis dalam era digital. Sebagai bagian dari budaya lisan, lagu rakyat Bugis mengalami perubahan signifikan ketika dihadapkan pada platform digital seperti YouTube dan media sosial. Penelitian ini menggunakan pendekatan kualitatif dengan teknik pengumpulan data berupa observasi, wawancara mendalam, dan studi dokumentasi. Hasil penelitian menunjukkan bahwa digitalisasi memungkinkan pelestarian lagu rakyat melalui rekaman audio-visual, namun sekaligus menggeser makna dan fungsi budaya lisan tersebut karena adanya proses komodifikasi. Lagu-lagu ini tidak lagi semata-mata berfungsi sebagai warisan budaya, tetapi juga sebagai produk ekonomi digital. Penelitian ini menyoroti pentingnya keseimbangan antara pelestarian nilai-nilai budaya dan adaptasi terhadap dinamika ekonomi digital.Kata kunci: budaya lisan, lagu rakyat, digitalisasi, komodifikasi